Pemeliharaan Website Desa Bulung Kulon untuk Optimalisasi Layanan E-Surat Administratif Bagi Masyarakat Secara Digital - Winny Apriliana; Kukuh Triyanto; Ilham Wijaya Kusuma; Evana Andriani (Universitas Muria Kudus, 2026)
Website maintenance is a strategic measure to support the seamless delivery of public services, particularly in the era of administrative digitalization. Bulung Kulon Village utilizes its official website as a platform for e-correspondence (e-surat) services, enabling residents to apply for various administrative documents online, rapidly, and efficiently. This article examines the stages of village website maintenance, including content updates, system troubleshooting, data security enhancement, and administrator training to ensure that e-correspondence services remain accessible and accurate. Through consistent maintenance, this digital administrative service is expected to increase transparency, accelerate communication processes, and strengthen the relationship between the village government and its citizens.